A model‐based solution for process modeling in practice environments: PLM4BS. Issue 12 (17th August 2018) - García‐García, Julián Alberto; García‐Borgoñón, Laura; Escalona, María José; Mejías, Manuel
Abstract: Today's world economic situation is ruled by issues such as reducing cost, improving quality, maximizing profit, and improving and optimizing processes at organizations. In this context, business process management can be an essential strategy, but it is not usually consolidated at software organizations because software process properties involve a complex business process management application on software lifecycle. Consequently, software organizations often focus on Software Process Modeling (SPM), and each involved role performs process execution and orchestration independently and manually. This fact makes software processes maintenance, monitoring, and measurement become difficult tasks. This paper proposes a model‐based approach for SPM taking into account concepts related to process execution, orchestration, and monitoring. It is framed into a model‐driven engineering‐based and tool‐based framework: Process Lifecycle Management for Business Software (PLM4 BS). We present a SPM metamodel and its concrete syntax (through Unified Modeling Language profiles) that lays the foundation for extending PLM4 BS. Its underlying metamodel allows managing processes automatically. Furthermore, PLM4 BS improves current state‐of‐the‐art proposals in 6 dimensions: expressiveness, understandability, granularity, measurability, orchestrability, and business variables and rules. Also, PLM4 BS has been evaluated in a multiple‐case study, in which the 6 mentioned dimensions were already validated.